Analysis of interface states and series resistance of Ag/SiO2/n-Si MIS Schottky diode using current-voltage and impedance spectroscopy methods - Okutan, Mustafa; Yakuphanoğlu, Fahrettin (Elsevier, 2008)
The electrical characteristics and interface state density properties of Ag/SiO2/n-Si metal-insulator-semiconductor diode have been analyzed by current-voltage and impedance spectroscopy techniques. The electronic parameters such as barrier height, ideality factor and average series resistance were determined and were found to be 0.62 eV, 1.91 and 975.8 Omega, respectively. The calculated ideality factor shows that Ag/SiO2/n-Si structure obeys a metal-interfacial layer-semiconductor configuration rather than ideal Schottky barrier diode. The interface state density of the diode is of order of similar to 10(11) eV(-1) cm(-2). The dielectrical relaxation mechanism of the diode is analyzed by Cole-Cole plots, indicating the presence of single relaxation mechanism. It is evaluated that the interfacial oxide layer modifies electrical parameters such as interface state density, series resistance and barrier height of Ag/SiO2/n-Si diode. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: metal-insulator-semiconductor diode; interfacial state density; AC conductance